SQL Injection Strategies: Practical techniques to secure old vulnerabilities against modern attacks - Galluccio, Ettore; Lombari, Gabriele; Caselli, Edoardo (Packt Publishing, 2020)
Learn to exploit vulnerable database applications using SQL injection tools and techniques, while understanding how to effectively prevent attacks Key Features * Understand SQL injection and its effects on websites and other systems * Get hands-on with SQL injection using both manual and automated tools * Explore practical tips for various attack and defense strategies relating to SQL injection Book Description SQL injection (SQLi) is probably the most infamous attack that can be unleashed against applications on the internet. SQL Injection Strategies is an end-to-end guide for beginners looking to learn how to perform SQL injection and test the security of web applications, websites, or databases, using both manual and automated techniques. The book serves as both a theoretical and practical guide to take you through the important aspects of SQL injection, both from an attack and a defense perspective. You'll start with a thorough introduction to SQL injection and its impact on websites and systems. Later, the book features steps to configure a virtual environment, so you can try SQL injection techniques safely on your own computer. These tests can be performed not only on web applications but also on web services and mobile applications that can be used for managing IoT environments. Tools such as sqlmap and others are then covered, helping you understand how to use them effectively to perform SQL injection attacks. By the end of this book, you will be well-versed with SQL injection, from both the attack and defense perspective. What you will learn * Focus on how to defend against SQL injection attacks * Understand web application security * Get up and running with a variety of SQL injection concepts * Become well-versed with different SQL injection scenarios * Discover SQL injection manual attack techniques * Delve into SQL injection automated techniques Who this book is for This book is ideal for penetration testers, ethical hackers, or anyone who wants to learn about SQL injection and the various attack and defense strategies against this web security vulnerability. No prior knowledge of SQL injection is needed to get started with this book.